Impact of Paraspinal Muscle Degeneration on Surgical Outcomes and Radiographical Sagittal Alignment in Adult Spinal Deformity: A Multicenter Study - Jun Ouchida; Yoshinori Morita; Sadayuki Ito; Naoki Segi; Ippei Yamauchi; Tokumi Kanemura; Tetsuya Ohara; Taichi Tsuji; Ryuichi Shinjyo; Shiro Imagama; Hiroaki Nakashima (Neurospine)
Objective This multicenter study aimed to evaluate the impact of paravertebral muscles (PVMs) degeneration, particularly fat infiltration, on preoperative sagittal imbalance, and postoperative complications and sagittal alignment change in patients with adult spinal deformity (ASD). Methods A retrospective analysis was conducted on 454 patients who underwent ASD surgery across 5 institutions. Patients were classified into 2 groups based on paraspinal muscle fat infiltration on MRI: those with significant infiltration (FI-PVM(+)) and those with minimal or no infiltration (FI-PVM(-)). Propensity score matching was performed to adjust for demographic factors and preoperative radiographical parameters. Spinopelvic parameters were assessed preoperatively, postoperatively, and at a 2-year follow-up. Mechanical complications were compared between the groups. Results The FI-PVM(+) group showed greater sagittal vertical axis (86.4 ± 57.5 vs. 51.8 ± 59.2, p < 0.001) preoperatively and required more extensive surgical correction with a significantly greater number of fused vertebral levels (7.3 ± 3.7 vs. 6.7 ± 3.7, p < 0.039). After propensity score matching, both groups showed significant improvement in spinopelvic alignment postoperatively, maintained throughout the 2-year follow-up. However, the FI-PVM(+) group demonstrated a trend toward a higher incidence of distal junctional kyphosis (6.3% vs. 0.9%, p = 0.070) and exhibited significantly greater decrease in pelvic tilt postoperatively (4.3° ± 7.6° vs. 1.3° ± 8.2°, p = 0.006). Conclusion Fat infiltration in PVM is associated with increased surgical complexity and a higher risk of mechanical complications. Preoperative assessment of muscle quality, along with targeted rehabilitation and closer postoperative monitoring, may be crucial for improving long-term outcomes in ASD surgery.